2010
DOI: 10.1111/j.1365-2656.2010.01731.x
|View full text |Cite
|
Sign up to set email alerts
|

How does local weather predict red deer home range size at different temporal scales?

Abstract: Summary1. There is a rapidly growing literature on how climate affects populations of vertebrates. For large herbivorous mammals, most attention has been paid to demographic responses to climate variation. Much less information is available regarding how climate affects animal behaviour, i.e. the climate mechanisms. Further, the appropriate measurement scale of climate variables remains debated. Here, we investigate how local climate variables determine home range sizes at four temporal scales using the Bo¨rge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
115
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(124 citation statements)
references
References 69 publications
5
115
4
Order By: Relevance
“…This supports the notion of different time scales capturing different phenomena [Kie et al, 2010;Rivrud et al, 2010]. A 16-month HR or CA may not include areas that are important for macaques over shorter temporal scales (days or weeks).…”
Section: Comparison Of Ranging Patterns With Other Related Macaque Spsupporting
confidence: 58%
See 2 more Smart Citations
“…This supports the notion of different time scales capturing different phenomena [Kie et al, 2010;Rivrud et al, 2010]. A 16-month HR or CA may not include areas that are important for macaques over shorter temporal scales (days or weeks).…”
Section: Comparison Of Ranging Patterns With Other Related Macaque Spsupporting
confidence: 58%
“…Several studies have measured site fidelity across multiple taxa [Asensio et al, 2012b;Burdett et al, 2007;Cords, 1987;Easley & Kinzey, 1986;Hellickson et al, 2008;Janmaat et al, 2009;Kitchen et al, 2000;Switzer, 1993]. Some authors consider that strong site fidelity reflects spatial stability in the location of resources for an animal over time whereas weak fidelity is the result of temporal shifts in the spatial distribution of resources [Doncaster & Macdonald, 1991;Kie et al, 2010;Rivrud et al, 2010]. Most studies of site fidelity have focused on territorial species in which individuals range in areas actively defended against conspecifics [e.g., Hellickson et al, 2008;Switzer, 1993;Wauters et al, 1995;Webb & Shine, 1997].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residents used comparable ranges during summer and autumn, while significantly expanding their space use in winter. This finding does not fit the general concept that climatic conditions influence ungulate spatial behaviour by reducing winter home range size as reported in red deer (Georgii and Schröder 1983;Koubek and Hrabe 1996), roe deer (Mysterud 1999;Rivrud et al 2010), moose (Phillips et al 1973;Thompson and Vukelish 1981) and ibex (Parrini et al 2003). However, Anderson et al (2005) reported that elk home ranges increased in winter and attributed this to predator pressure of wolves, population densities and reduced quantity and quality of forage.…”
Section: Discussionmentioning
confidence: 71%
“…For example, the spatial distribution of Thomson's gazelles Gazella thomsonii in Africa continually changing from month to month, like a shifting mosaic [50]. Similarly, home-range size of red deer Cervus elaphus at multiple temporal scales is driven by temporally dynamic variables such as temperature, precipitation, day length and snow cover [51]. Hence, studies of animal movements can greatly benefit from the incorporation of temporally dynamic environmental variables.…”
Section: Discussionmentioning
confidence: 99%